2015
DOI: 10.1016/j.still.2015.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Cover crop and tillage systems effect on soil CO2 and N2O fluxes in contrasting topographic positions

Abstract:  Sensitivity of CO 2 emissions to soil temperature was higher in cover crop than no cover 7 crop treatments. 8 CO 2 emissions from the ridge tillage were higher than from the chisel tillage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 68 publications
2
25
0
Order By: Relevance
“…Although the late‐terminated CC produced greater biomass, this is only about half the residue produced by corn (9–11 Mg ha −1 ) (Ruis et al, 2017). The increased CO 2 flux under the late‐terminated CC is possibly due to both plant respiration and microbial activity on fresh organic matter (i.e., heterotrophic respiration) (Liebig et al, 2010; Negassa et al, 2015); however, separating soil and plant respiration is difficult. The literature review also suggests that CCs are more likely to change plant + soil respiration during the CC period than after CC termination or the main crop period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the late‐terminated CC produced greater biomass, this is only about half the residue produced by corn (9–11 Mg ha −1 ) (Ruis et al, 2017). The increased CO 2 flux under the late‐terminated CC is possibly due to both plant respiration and microbial activity on fresh organic matter (i.e., heterotrophic respiration) (Liebig et al, 2010; Negassa et al, 2015); however, separating soil and plant respiration is difficult. The literature review also suggests that CCs are more likely to change plant + soil respiration during the CC period than after CC termination or the main crop period.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating gas fluxes under different CC termination dates are very few. In many studies, CCs are terminated early with low biomass production (<1 Mg ha −1 ), which may reduce gas fluxes (Negassa et al, 2015; Thomas et al, 2017). For example, Negassa et al (2015) showed that CO 2 and N 2 O fluxes were not affected when CC biomass yield was below 0.5 Mg ha −1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, many studies did not report basic soil information and very few considered interactions between the management practices and ecosystem state factors. For instance, while many studies recognized the importance of landscape characteristics on N 2 O emissions (Corre et al 1996;Castellano et al 2010;Vilain et al 2010;Gu et al 2011;Li et al 2012;Schelde et al 2011) only few examined the interaction between landscape characteristics and management strategies (Sehy et al 2003;Izaurralde et al 2004;Negassa et al 2015). Sehy et al (2003) found that adjusting fertilizer rates for different landscape positions was effective at reducing N 2 O.…”
Section: Ecologically-based Nutrient Management Practicesmentioning
confidence: 99%
“…Results of studies on the effect of tillage on N 2 O emissions are contradictory. When compared to conventional tillage, RT reduced N 2 O emissions ( i.e ., Koga , ; Wang and Dalal , ), resulted in similar N 2 O emissions ( i.e ., Abdalla et al., ; Negassa et al., ) or, which was the majority of experiments, increased emission ( i.e ., Baggs et al., ; Venterea et al., ). Lognoul et al.…”
Section: Introductionmentioning
confidence: 95%